If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
y-((1/3)*x) = 0
(-1/3)*x+y = 0
y-1/3*x = 0 // - y
-1/3*x = -y // : -1/3
x = -y/(-1/3)
x = 3*y
x = 3*y
| D-35=50 | | 10(0.6x+4)=10(0.3x+7) | | 2x/(x-3)=8 | | 1521=39(p+10) | | A-3=24 | | 10=17+b | | 3v+12=63 | | X-100=-10 | | p^6/p^4= | | 28=17-r | | Y-150=15 | | -3x-9+7x+27=11x+9-2x | | 33=20+k | | A-15=25 | | 3080=44(p+25) | | 4/3y-8=24 | | 930=5(x+17) | | -m-28=-4(2-m) | | 6+2ln(4x)=12 | | 3x^2-30=4 | | 3(11/2-1/8) | | 203=7(8-7x) | | 1/3x-9=3 | | 1/3x-9=3 | | 5+2m+6=3 | | 19-(13x+4)=12-3x-(5x+2) | | 144+8m=264 | | 5m+2m=0 | | fm+2m=0 | | -8b+4(5-3b)=20+6b | | 23n-96=272 | | X^4+6x+4=0 |